Genome-editing applications of CRISPR–Cas9 to promote in vitro studies of Alzheimer’s disease - Giau VV (Dove Medical Press, 2018)
Vo Van Giau,1,* Hyon Lee,2,* Kyu Hwan Shim,1 Eva Bagyinszky,1 Seong Soo A An1 1Department of Bionano Technology, Gachon University, Seongnam, South Korea; 2Department of Neurology, Gachon University Gil Medical Center, Incheon, South Korea *These authors contributed equally to this work Abstract: Genetic variations play an important role in the clinical presentation and progression of Alzheimer’s disease (AD), especially early-onset Alzheimer’s disease. Hundreds of mutations have been reported with the majority resulting from alterations in β-amyloid precursor protein (APP), presenilin 1 (PSEN1), or presenilin 2 (PSEN2) genes. The roles of these mutations in the pathogenesis of AD have been classically confirmed or refuted through functional studies, where the mutations are cloned, inserted into cell lines, and monitored for changes in various properties including cell survival, amyloid production, or Aβ42/40 ratio. However, these verification studies tend to be expensive, time consuming, and inconsistent. Recently, the clustered regularly interspaced short palindromic repeats-CRISPR-associated protein 9 (CRISPR–Cas9) system was developed, which improves sequence-specific gene editing in cell lines, organs, and animals. CRISPR–Cas9 is a promising tool for the generation of models of human genetic diseases and could facilitate the establishment of new animal AD models and the observation of dynamic bioprocesses in AD. Here, we recapitulated the history of CRISPR technology, recent progress, and, especially, its potential applications in AD-related genetic, animal modeling, and functional studies. Keywords: Alzheimer’s disease, CRISPR–Cas9, mutation, Aβ42/40 ratio